Influence of the properties of secondary α-titanium casts, obtained by chamberless electroslag casting, for processing by turning - Bilonyk, Dmytro; Kapustian, Oleksii; Kanashevych, Heorgii; Laptieva, Hanna; Hubar, Yevheniy; Bilonyk, Igor (Technology audit and production reserves, 2025)
The object of the study is the machinability by turning of secondary α-titanium casts produced via chamberless electroslag remelting (CESR) (hereinafter referred to as secondary α-titanium), using non-consumable electrodes fabricated from 100% VT1-0 titanium scrap. One of the most challenging issues is the difficulty of machining both primary and secondary titanium. Specifically, this includes chip adhesion to the cutting tool due to the high plasticity of titanium alloys and increased contact surface temperatures, which lead to oxidation. The study employed modern metallographic methods to examine the macrostructure, chemical composition, and mechanical properties of α-titanium; experimental methods were used to determine optimal turning conditions; and the machinability coefficient was determined using graphical interpolation. Tool wear resistance was evaluated by comparative methods. Optimal machining parameters were established for the removal of the alpha-case layer and achieving a surface roughness of classes 5–8: cutting speed V = 25–30 mm/min; feed rate S = 0.5–0.9 mm/rev; cutting depth T = 1.0–1.2 mm. The selected turning regimes enable the production of complex threaded profiles in accordance with ISO 724:1993 requirements. The study demonstrated that turning secondary α-titanium casts does not require additional technological measures or high-wear-resistant specialized tools. The machinability coefficient was determined to be 0.47–0.48. The improved machinability of the secondary α-titanium casts is attributed to the high quality of the metal, ensured by droplet-based metal transfer and consistent crystallization in a water-cooled copper mold, resulting in higher density and structural homogeneity. The application of chamberless electroslag casting technology enhanced the quality of α-titanium and expanded the potential for its use in the manufacturing of parts for mechanical engineering, chemical, and aerospace industries. Producing secondary α-titanium using titanium scrap through this technology allows a reduction in production cost by approximately 25–30%.